Empowering character building-based education: Discourse analysis on official English textbook - Nida Husna; Tahnia Lestari (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2019)
AbstractPancasila is the ideology of the nation and becomes the foundation of Indonesian characters. However, based on the reality, there were many Indonesian’s characters that are far below expectation of the standard in Butir-butir Pancasila (Items of Pancasila), as a further explanation of the values in Pancasila. Therefore, it is needed to introduce of Pancasila and its 45 items in our formal education system. Textbook still become the primary media formal education schools. By assessing several books which were published by distinguished publishers and used in schools, it was found that they included only a very few of those items. This study was held to know if character points of Pancasila which Indonesian learners need to know have been included in the textbooks titled When English Rings the Bell: Buku Siswa and When English Rings the Bell: Buku Guru which were officially published by the Educational and Cultural Ministry of Indonesia and used the primary textbook in models schools as the implementation of Kurikulum 2013. The findings showed that as the official textbook has adequate number of Pancasila items in it. However, the teachers’ role was still the most important factor to make those items were known and can be applied.AbstrakPancasila adalah ideologi bangsa dan menjadi fondasi karakter Indonesia. Namun, berdasarkan kenyataan, ada banyak karakter Indonesia yang jauh di bawah ekspektasi standar dalam Item Pancasila, sebagai penjelasan lebih lanjut tentang nilai-nilai dalam Pancasila. Oleh karena itu, perlu untuk memperkenalkan Pancasila dan 45 poinnya dalam sistem pendidikan formal kita. Buku teks masih menjadi media pendidikan formal sekolah dasar. Dengan menilai beberapa buku yang diterbitkan oleh penerbit terkemuka dan digunakan di sekolah-sekolah, ditemukan bahwa mereka hanya memasukkan sedikit dari barang-barang itu. Penelitian ini diadakan untuk mengetahui apakah poin-poin karakter Pancasila yang perlu diketahui oleh pelajar Indonesia telah dimasukkan dalam buku teks berjudul When English Rings the Bell: Books Student and When English Rings the Bell: Books's Teacher yang secara resmi diterbitkan oleh the Educational and Kementerian Kebudayaan Indonesia dan menggunakan buku teks utama di sekolah-sekolah model sebagai implementasi dari Kurikulum 2013. Temuan menunjukkan bahwa sebagai buku teks resmi memiliki jumlah beberapa poin Pancasila yang memadai di dalamnya. Namun, peran guru masih merupakan faktor terpenting untuk membuat item-item itu diketahui dan dapat diterapkan. How to Cite : Husna, N., Kamar, T. L.. (2019). Empowering Character Building-Based Education: an Evaluation on Official English Textbook. TARBIYA: Journal of Education in Muslim Society, 6(1), 58-68. doi:10.15408/tjems.v6i1.10354.